Symmetry in the vanishing of Ext over Gorenstein rings - Huneke, Craig; Jorgensen, David A. (MATHEMATICA SCANDINAVICA, 2003)
We investigate symmetry in the vanishing of Ext for finitely generated modules over local Gorenstein rings. In particular, we define a class of local Gorenstein rings, which we call AB rings, and show that for finitely generated modules M and N over an AB ring R, Ext^i_R(M,N)=0 for all i0 if and only if Ext^i_R(N,M)=0 for all i0.